Grafting on Polystyrene on Different Parts of the Molecule and Determination of Metal Uptake Thereby - Temuz, Mehmet Mursit (Taylor & Francis Inc, 2022)
alpha-Br-polystyrene (Br%7PS) and polystyrene p-acetyl chloride (Cl%5PS) were obtained by modification of polystyrene on its main chain and side groups using N-bromosuccinimide and acetyl chloride, respectively. The graft copolymers were prepared via atom transfer radical polymerization (ATRP) with Br%7PS and Cl%5PS as the macro-initiators, methacrylamide (MA) as monomer, 1,2-dipiperidinoethane as ligand, and CuBr as a transition metal compound. Characterization of the reaction products was done using Fourier transform infrared (FTIR) spectroscopy, H-1 proton nuclear magnetic resonance (H-1-NMR) spectrometry and elemental analyses. According to the results of the structure characterization, the percentages of substitution of styrene units in the polystyrene were found to be 7.14% for Br%7PS and 5.21% for Cl%5PS by moles. The uptake properties of various metal ions by the polymers were investigated by an atomic absorption spectrophotometer (AAS).
Keywords: atom transfer radical polymerization; grafted polystyrene; metal uptake